Savanna hypothesis in the human-urban nature relationship - Hartsell, Angela Marie (Emerald Group Publishing Ltd, 2021)
Purpose This paper expounds theoretical reasons behind and practical applications of urban natural space as part of the ontological whole of the city. Design/methodology/approach In this paper, nonsecular and secular relationships between humans and nature are explored from an ontological perspective. Findings The characteristics of the savanna hypothesis are shown to be tectonic elements that have been used historically in human-defined landscapes and can be implemented in urban planning and design to enhance urban green spaces and improve the overall quality of urban life. Social implications The human-nature relationship has morphed and adapted as civilizations and their belief systems have grown and fallen aside. The human-nature relationship has affected the form of cities while human development and technological advancements have affected nature's representation in the urban realm. Throughout the periods of nonsecular affection for nature and secular applications of nature, one theme has persisted: human innate preference for certain arrangements of certain natural elements. Though existing long before the first human settlements were formed, the savanna hypothesis was not coined until the 20th century. Originality/value Ultimately, the savanna hypothesis is exhibited as a joining concept that connects nonsecular affection for nature to secular qualities of urban nature and natural infrastructure.
Keywords: Savanna hypothesis; Secularity; Human-nature relationship; Urban natural space; Natural infrastructure; Urban design; Socially and culturally sustainable architecture and urban design; Urban green space; Urban green infrastructure